Concurrent training and reflection model (CTRM) for in-service teachers - Noora Al-Thani; Zubair Ahmed; Jolly Bhadra (Frontiers in Education, 2025)
This study investigates the effectiveness of the Concurrent Training and Reflection Model (CTRM) in enhancing the research competencies of in-service teachers. CTRM integrates structured research methodology training with real-time classroom reflection, enabling teachers to apply their learning immediately and evaluate its impact through student outcomes. Seventeen teachers from public schools in Qatar participated in a ten-session training program over 60 days. Each teacher guided a minimum of 20 students in conducting research-based projects, involving a total of 347 students. The study employed an exploratory sequential mixed-methods design, grounded in Research Cognitive Theory (RCT), and guided by Kirkpatrick’s Four-Level Evaluation Model. Data were collected through an ad hoc pre-post questionnaire, developed and validated by the research team based on stakeholder interviews and focus group discussions. The researchers used quantitative data to assess changes in teachers’ research knowledge and ability, while qualitative data included teacher reflections, facilitator feedback, and student outputs provided contextual insights. During the reflection phase, students worked in small groups designing posters and STEM prototypes, which were evaluated at the school level. One prototype and one presentation from each school were selected for final presentation and evaluation, resulting in 17 shortlisted entries. The results demonstrated significant improvements in teachers’ research competencies, including their conceptual knowledge, practical application skills, and attitudes toward research. Student-generated outputs provided tangible evidence of instructional impact and reflective teacher growth. The CTRM model proved effective in promoting inquiry-based teaching and fostering a research-oriented classroom culture.